Microsoft 70-247 : configuring and deploying a private cloud with System Center 2012 - Riggs, Ann; Safari eBooks ([Place of publication not identified] : iCollege, 2017)
"The new Configuring and Deploying a Private Cloud with System Center 2012 course provides full coverage of the knowledge and skills required to pass the Microsoft exam 70-247 Some of the skills you will learn in this class are: Design a scalable System Center architecture Install the System Center Infrastructure Upgrade System Center components Configure System Center components Configure portals and dashboards Configure the storage fabric Configure the network fabric Configure and manage the deployment and update servers Configure clouds and virtualization hosts Configure private cloud integration Configure integration of private and public clouds Configure profiles Create and configure server App-V packages Configure and deploy a service Update a service."--Resource description page.
Presenter, Ann Riggs.
Title and publication information from resource description page (Safari, viewed March 3, 2017).
Keywords: Microsoft System center -- Certification -- Study guides; Cloud computing -- Certification; Computer technicians -- Certification -- Study guides; Electronic books